COMBINATORIAL EFFECT OF LEPTIN, TUMOR NECROSIS FACTOR-Î‘LPHA, AND VITAMIN D IN PROGRESSION OF TYPE 2 DIABETES IN KASHMIRI POPULATION - Din, Inshah; Majid, Sabhiya; Rashid, Fouzia; Hussain, Ishrat; Koul, Rakesh K; Qadir, Jasiya; Farooq, Rabia (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Type 2 diabetes mellitus (T2DM) is a metabolic disorder usually characterized by hyperglycemia. Adipose tissue secretes bioactive substances known as adipocytokines including leptin, tumor necrosis factor-alpha (TNF-Î±), and adiponectin. These are considered as a bridge connecting obesity and insulin resistance. There is considerable epidemiological evidence to suggest a role of Vitamin D deficiency in the etiology of T2DM. This study was performed to evaluate and compare serum Vitamin D and adipocytokine levels in T2DM patients and healthy controls of Jammu and Kashmir region of India. Methods: A total of 200 T2DM patients and normal 200 healthy controls were considered for the study. Enzyme-linked immunosorbent assay was used to measure serum leptin and TNF-Î± levels. The Vitamin D levels were measured by chemiluminescent microparticle immunoassay method. Biochemical parameters were measured by the enzymatic method. Results: Our results concluded that basic metabolic parameters, TNF-Î± and leptin levels were significantly higher in cases than controls. The serum Vitamin D levels were found significantly lower among T2DM patients. No correlation of Vitamin D with leptin was observed in cases and controls. However, a positive correlation between leptin and TNF-Î± was noted in T2DM subjects as well as in controls with statistical significance being higher in females (r=0.500; p=0.001) as compared to males (r=0.298; p=0.036) in T2DM subjects as well as in controls (r=0.659; p=0.001; r=0.621; p=001). Conclusion: These results concluded that lowering of Vitamin D levels and upregulation of leptin and TNF-Î± altogether play an important role in the development of T2DM, and from correlation analysis, it could be predicted that leptin and TNF-Î± act in a synergistic manner toward the development of T2DM.